(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The proximate, sugar, minerals and fatty acids composition of date palm fruit were determined. The moisture content is 5.24 ± 0.05%, ether extract value is 1.54 ± 0.01%, crude fibre content is 4.34+ 0.03%, crude protein content is 4.94+0.04% while the value of carbohydrate is 80.87 ± 0.05%. The fractions of sugar contained maltose (33.7mg%), fructose (22.8mg%) and glucose (22.3mg%). The most abundant minerals in the sample is potassium with the value of 710.0 mg% sample. The most concentrated fatty acids were oleic acid (44.51g/100g) > palmitic acid (23.05g/100g) > linoleic acid (11.66g/100g). All these quality food properties make it good source of unsaturated fatty acids and sweetening agent in food processing industry. Key words: Carbohydrates; Fatty acids; Minerals; Fruit flour. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8194 Bangladesh J. Sci. Ind. Res. 46(2), 255-258, 2011